SOME RESULTS OBTAINED ON THE STUDY OF THE CHEMICAL COMPOSITION OF EURASIAN OILS DEPENDING ON THE DEPTH AND AGE OF THE RESERVOIR ROCK - Ahn V.V.; Polichtchouk Y.M.; Yashchenko I.G. (My University, 2002)
The sulfur, paraffin, resin and asphaltene contents of some 6570 Cenozoic, Mesozoic and Paleozoic Eurasian oils were analysed statistically in terms of reservoir age and depth. The database includes all principal oil-bearing basins from 60 Eurasian countries. The results of the studies of the relationships between the distribution of oils with different sulfur, paraffin, resin and asphaltene contents and the reservoir age and depth are presented. Predictive trends are established allowing polynomial predictions of average properties.